Comparative Transcriptomic Analysis of Two Actinorhizal Plants and the Legume Medicagotruncatula Supports the Homology of Root Nodule Symbioses and Is Congruent With a Two-Step Process of Evolution in the Nitrogen-Fixing Clade of Angiosperms - Battenberg, Kai; Potter, Daniel; Tabuloc, Christine A.; Chiu, Joanna C.; Berry, Alison M. (Frontiers in Plant Science, 2018)
Root nodule symbiosis (RNS) is a symbiotic interaction established between angiosperm hosts and nitrogen-fixing soil bacteria in specialized organs called root nodules. The host plants provide photosynthate and the microsymbionts supply fixed nitrogen. The origin of RNS represents a major evolutionary event in the angiosperms, and understanding the genetic underpinnings of this event is of major economic and agricultural importance. Plants that engage in RNS are restricted to a single angiosperm clade known as the nitrogen-fixing clade (NFC), yet occur in multiple lineages scattered within the NFC. It has been postulated that RNS evolved in two steps: a gain-of-predisposition event occurring at the base of the NFC, followed by a gain-of-function event in each host plant lineage. Here we first explore the premise that RNS has evolved from a single common background, and then we explore whether a two-step process better explains the evolutionary origin of RNS than either a single-step process, or multiple origins. We assembled the transcriptomes of root and nodule of two actinorhizal plants, Ceanothus thyrsiflorus and Datisca glomerata. Together with the corresponding published transcriptomes of the model legume Medicago truncatula, the gene expression patterns in roots and nodules were compared across the three lineages. We found that orthologs of many genes essential for RNS in the model legumes are expressed in all three lineages, and that the overall nodule gene expression patterns were more similar to each other than expected by random chance, a finding that supports a common evolutionary background for RNS shared by the three lineages. Moreover, phylogenetic analyses suggested that a substantial portion of the genes experiencing selection pressure changes at the base of the NFC also experienced additional changes at the base of each host plant lineage. Our results (1) support the occurrence of an event that led to RNS at the base of the NFC, and (2) suggest a subsequent change in each lineage, most consistent with a two-step origin of RNS. Among several conserved functions identified, strigolactone-related genes were down-regulated in nodules of all three species, suggesting a shared function similar to that shown for arbuscular mycorrhizal symbioses.